Coadministration of Liposomal Amphotericin B and Contrast Medium Does Not Increase Risk of Kidney Injury - O'Horo, John C. (Antimicrob Agents Chemother, 2017)
Intravenous radiographic contrast medium and amphotericin B are commonly required in the care of patients with fungal infections. Both interventions have proposed nephrotoxicity through similar mechanisms. We systematically examined patients who received coadministration of liposomal amphotericin B (AmBisome; GE Healthcare) and intravenous contrast medium within a 24-h period and compared the results for those patients with the results for patients who underwent non-contrast medium studies. We found 114 cases and 85 controls during our study period. Overall, no increased risk of renal injury was seen with coadministration of these 2 agents. Adjustment for age, baseline kidney function, and other clinical factors through propensity score adjustment did not change this result. Our observations suggest that, when clinically indicated, coadministration of contrast medium and liposomal amphotericin B does not present excess risk compared with that from the administration of liposomal amphotericin B alone.